دراسة تأثير غبار معمل إسمنت طرطوس في النوع Citrus jaffer (البرتقال اليافاوي) - خوري, مارييل; مصطفى, سوزان; حداد, دينا (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة تأثير غبار معمل إسمنت طرطوس في الخصائص المورفولوجية والفيزيولوجية لنوع البرتقال اليافاوي (Citrus jaffer) في ثلاث مناطق . المنطقة الأولى تقع في وطى الحصين وهي أكثر المناطق تلوثاً لوقوع المعمل فيها.المنطقة الثانية في قرية بعشتر وتقع شمال شرق المعمل، وهي أقل تلوثاً من الأولى،أما المنطقة الثالثة فهي في الجدّيدة والتي تبعد عن المعمل حوالي 9 كم وبالتالي هي المنطقة الأقل تلوثاً. بينت نتائج الدراسة، أنه كلما ازداد القرب من المعمل كلما ازدادت حمولة الأوراق من الغبار، وكلما نقص وزنها وطولها ومساحتها، وكذلك انخفض محتوى كل من الكلوروفيل a،الكلوروفيل a+ b والنسبة a / b وازداد تركيز الكلورفيل b، وانخفض المحتوى المائي للأوراق وكذلك محتواها من السكريات .كما لوحظ أثر التلوث في نمو الجهاز التكاثري إذ تناقصت أطوال القطع الزهرية ونسبة عدد حبات الطلع الكبيرة للصغيرة وانخفضت حيويتها، كذلك أدى التّلوث بالغبار لإنخفاض أبعاد الثمار وأوزانها وحجم العصيرفي الثمرة وتركيز السكريات االمنحلة فيه. The effect of Tartos cement factory's dust on the morphological and physiological traits of Citrus jaffer has been studied in three areas: The first area in Wata Al Hsein is the most polluted one because of the fact that the cement factory is situated there. The second area is Bashtar Village to the north east of the factory and is less polluted than the first one. The third area, Al-jdeideh, is at a distance of 9 km from the factory and is consequently the least polluted among the three. The result has shown that the trees closer to the factory carried more cement dust on the leaves, and the cement dust caused decrease in the leaf 's length ,weight and area ( size) and reduces the amount of chl a ,chl a+b, and chla\chlb contents ,increase the chl b content, amount of water in the leaf and carbohydrate content also decreases. Besides, the impact of pollution on the proliferative, the growth of floral parts has observed and the proportion of large pollen to small ones and vitality have been decreased .Pollution has also led to a decrease in each of the dimensions and weight of fruits, juice content and concentration of soluble sugars in it.